Offshoring and backshoring: A multiple case study analysis. Issue 2 (March 2018) - Di Mauro, Carmela; Fratocchi, Luciano; Orzes, Guido; Sartor, Marco
Abstract: Motivations underscoring offshoring and backshoring are typically investigated as separate entities in the academic literature. This separation undermines a deeper comprehension of the two phenomena, and implicitly denies the conceptualization of backshoring as a possible step of the firm internationalization process. Our paper seeks to fill this gap by (1) understanding the relations (if any) among offshoring and backshoring motivations at firm level; (2) exploring whether backshoring is a "failure" of the offshoring initiative, or rather the evolution of the firm's competitive and location strategies. A content-based literature review provides the base for the identification of the key motives for offshoring and backshoring, which are then organised using a theory-grounded framework. Next, we conduct a multiple case study analysis based on four companies, searching for common patterns in offshoring and subsequent backshoring initiatives. Cases allow understanding how the motivations (Why) connect with the governance modes (How), and the location choice (Where). Building on the case findings, the paper presents some propositions for future empirical research. Highlights: We review extant literature on offshoring and backshoring motivations. We investigate links between offshoring and backshoring through case-study analysis. We apply a theoretical framework to interpret offshoring/backshoring motivations. We link motivations to governance modes and production location decisions.